Toe Tissue Transfer for Reconstruction of Damaged Digits due to Electrical Burns - Hyung-Do Kim (Archives of Plastic Surgery, 2012)
Background Electrical burns are one of the most devastating types of injuries, and can be characterized by the conduction of electric current through the deeper soft tissue such as vessels, nerves, muscles, and bones. For that reason, the extent of an electric burn is very frequently underestimated on initial impression. Methods From July 1999 to June 2006, we performed 15 cases of toe tissue transfer for the reconstruction of finger defects caused by electrical burns. We performed preoperative range of motion exercise, early excision, and coverage of the digital defect with toe tissue transfer. Results We obtained satisfactory results in both functional and aesthetic aspects in all 15 cases without specific complications. Static two-point discrimination results in the transferred toe cases ranged from 8 to 11 mm, with an average of 9.5 mm. The mean range of motion of the transferred toe was 20° to 36° in the distal interphalangeal joint, 16° to 45° in the proximal interphalangeal joint, and 15° to 35° in the metacarpophalangeal joint. All of the patients were relatively satisfied with the function and appearance of their new digits. Conclusions The strategic management of electrical injury to the hands can be both challenging and complex. Because the optimal surgical method is free tissue transfer, maintenance of vascular integrity among various physiological changes works as a determining factor for the postoperative outcome following the reconstruction.